PENGARUH GOOD CORPORATE GOVERNANCE TERHADAP TAX AVOIDANCE (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2018-2019) - Tedo Arsa Nanditama; Moh Didik Ardiyanto (Diponegoro Journal of Accounting, 2021)
This study aims to examine the effect of good corporate governance consisting of executive character, firm size, leverage, liquidity, institutional ownership, managerial ownership, independent board of commissioners, board of directors, audit committee, audit committee meeting, and audit quality on measured tax avoidance. with ETR.The population in this study consisted of all manufacturing companies listed on the Indonesia Stock Exchange in the 2018-2019 period. Sampling was done by using purposive a sampling method. The total sample of this research is 103 companies. To test the hypothesis, this study uses multiple regression analysis.The results of this study indicate that firm size, institutional ownership and managerial ownership have a significant positive effect on tax avoidance. In addition, leverage and audit quality have a significant negative effect on tax avoidance. As for the character of the executive, liquidity, independent board of commissioners, board of directors, audit committee and audit committee meetings have no significant effect on tax avoidance.